2016
DOI: 10.1038/srep34154
|View full text |Cite
|
Sign up to set email alerts
|

Non-cell autonomous cues for enhanced functionality of human embryonic stem cell-derived cardiomyocytes via maturation of sarcolemmal and mitochondrial KATP channels

Abstract: Human embryonic stem cells (hESCs) is a potential unlimited ex vivo source of ventricular (V) cardiomyocytes (CMs), but hESC-VCMs and their engineered tissues display immature traits. In adult VCMs, sarcolemmal (sarc) and mitochondrial (mito) ATP-sensitive potassium (KATP) channels play crucial roles in excitability and cardioprotection. In this study, we aim to investigate the biological roles and use of sarcKATP and mitoKATP in hESC-VCM. We showed that SarcIK, ATP in single hESC-VCMs was dormant under baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…the downregulation of their molecular correlates HCN2 and HCN4. As for Ca 2+ handling, which is of central importance to excitation-contraction coupling, such related gene products as PLN and SERCA were upregulated, leading to improved calcium handling and subsequent contractility (Keung et al, 2016;Li et al, 2019). Other groups have reported similar findings where electrical pacing in hiPSC-CM tissue constructs promoted contractile force by ∼20-fold along with ∼2-and ∼1.5-fold increases in protein expression of SERCA and RYR, respectively, when compared to untreated controls (Ruan et al, 2016) or sensitivity toward isoproterenol, as indicated by calcium imaging (Ronaldson-Bouchard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the downregulation of their molecular correlates HCN2 and HCN4. As for Ca 2+ handling, which is of central importance to excitation-contraction coupling, such related gene products as PLN and SERCA were upregulated, leading to improved calcium handling and subsequent contractility (Keung et al, 2016;Li et al, 2019). Other groups have reported similar findings where electrical pacing in hiPSC-CM tissue constructs promoted contractile force by ∼20-fold along with ∼2-and ∼1.5-fold increases in protein expression of SERCA and RYR, respectively, when compared to untreated controls (Ruan et al, 2016) or sensitivity toward isoproterenol, as indicated by calcium imaging (Ronaldson-Bouchard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade or so, significant progress has been made in ventricular (V) specification to obtain high-purity VCMs (Ebert et al, 2012;Spater et al, 2014;Weng et al, 2014) for cardiac tissue engineering (Tallawi et al, 2015;Kolanowski et al, 2017;Wong et al, 2019). However, human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) possess immature fetal-like properties (Lieu et al, 2013;Robertson et al, 2013;Poon et al, 2015;Keung et al, 2016;Kadota et al, 2017;Ronaldson-Bouchard et al, 2019). Electrophysiologically, hPSC-CMs spontaneously fire action potentials (AP) with slower kinetics, starkly contrasting their quiescent-yet-excitable adult counterparts (Lieu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the designs are based on specific tissue-engineered formats using methods such as SU-8 photolithography 22,23 , bioprinting 24,25 , decellularization of whole hearts 26 , surface micropatterning [27][28][29] , biowires 23,30 , or casting molds as hydrogel (collagen, Matrigel or fibrinogens) scaffolds 22,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . Engineered heart tissues (EHTs) are grown on mechanical supports or pillars providing mechanical load and have been described to induce hiPSC-CM maturation 35,37 .…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…One system uses forced supraphysiological pacing up to 6 Hz to facilitate this 40 . The initial designs 48 were low-throughput, time-consuming and costly for both academic laboratories and pharma but miniaturized versions have now been made 22,30,34,36,42,45,47 .…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…The platform can be adapted to single cells, anisotropic sheets, and tissue strips. Their human ventricular cardiac organoid chambers provide a comprehensive bioreactor model enabling force and electrophysiology measurements with minimal manipulation [ 130 ].…”
Section: Advanced Technologies and Tissue Engineering: Novel Appromentioning
confidence: 99%